YURISDIKSI THE MECHANISM FOR INTERNATIONAL CRIMINAL TRIBUNALS (MICT) TERHADAP KEJAHATAN HAM BERAT YANG DILAKUKAN RATKO MLADIĆ PADA SAAT KONFLIK BERSENJATA DI BOSNIA-HERZEGOVINA - Yogie Indra Kurniawan; Ayub Torry Satrio Kusumo (BELLI AC PACIS, 2016)
This research purpose to analysis Ratko Mladić kind of violations of human right in Bosnia-Herzegovina 1992-1995 and law enforcement mechanism against Ratko Mladić who caught in 2011. This research is the normative legal research is prescriptive and applied approach to the conceptual approach, statute approach and  cases approach. The research results showed that Ratko Mladić did severe human rights violations; 1) genocide, 2) crimes againt humanity, 3) war crimes and There are two mechanisms for conducting law enforcement to Ratko Mladić who have committed human rights violations. First by using the national mechanisms, second using Ad Hoc MICT Court instead of an Ad Hoc Court of the ICTY mandate has been completed in 2010.